Dual effects of family ritual communication on Chinese adolescents’ well-being: supportive and constraining mechanisms - Zhibin, Ban; Li, Qiu; Yulin, Cai; Chunxiaoyu, Wu (Frontiers in Psychology, 2025)
BackgroundAdolescent well-being has garnered significant attention from researchers both domestically and internationally. Much research focuses on the connection between adolescent well-being and family dynamics. As the main source of social support, the family significantly influences adolescent well-being. Western studies have identified family ritual communication as a crucial factor that can exert both positive and negative effects on adolescent well-being. However, most studies are contextualized within Western societies, and their findings may not be directly applicable to Chinese social settings.MethodsThis research employed a questionnaire survey method to examine the impact of family ritual communication on the well-being of Chinese adolescents. A pilot survey was conducted to validate the questionnaire’s design before administering the final version. Initially, 150 questionnaires were distributed, yielding 144 valid responses. Following reliability and validity testing, a formal survey was conducted involving 848 adolescents aged 14 to 18. After eliminating responses with overly regular patterns, 755 valid questionnaires were retained.ResultsThe study elucidated the mechanisms through which family ritual communication affects the subjective well-being of Chinese adolescents, summarizing these effects as a form of psychological empowerment characterized by “support and constraint.” Family ritual communication serves as a supportive element, enhancing adolescent well-being through two mediators: family intimacy and resilience. Conversely, this form of psychological empowerment can also constrain adolescent well-being due to intergenerational power dynamics. Notably, the interdependent self-concept did not moderate the relationship between family ritual communication and the adolescents’ subjective well-being.